Detection of Onion Yellow Dwarf Virus (OYDV) in Onion Commodities Using DAS-ELISA and RT-PCR at The Point of Entry for Carrier Media at Semayang Port, Balikpapan - Zulverdi, Yudhika Tsabitah Ramacendani; Martosudiro, Mintarto (University of Brawijaya, 2026)
Plants of the genus Allium, such as shallots (Allium cepa var. aggregatum), garlic (Allium sativum L.), green onions (Allium fistulosum L.), and onions (Allium cepa var. cepa), are high-value commodities widely consumed in Indonesia. However, Allium production in East Kalimantan does not meet local demand, necessitating supplies from other regions. This inter-regional transport poses a risk of introducing organisms harmful to plants. Among these pests, viruses are particularly challenging to control. According to the Regulation of the Minister of Agriculture No. 25 of 2020, Onion Yellow Dwarf Virus is classified as a quarantine pest under category A2 requiring strict monitoring in Indonesia. Its distribution is currently limited to Java, Bali, West Nusa Tenggara, and Sulawesi. Therefore, accurate detection techniques are critical to prevent the spread of this pathogen to areas still free from Onion Yellow Dwarf Virus. Research results indicate that among the four types of onions, Onion Yellow Dwarf Virus (OYDV) exhibits symptoms in garlic. This finding was also confirmed through DAS-ELISA and RT-PCR testing. The detection results using DAS-ELISA on garlic plants showed an ELISA Reader absorbance value (0.6848) greater than twice the absorbance value of the negative control (0.2982). RT-PCR detection also yielded positive results with the formation of a 500 bp band.